Sense of Community dalam Memediasi Hubungan Kepemimpinan dan Konflik Peran dengan Kepercayaan Anggota Organisasi Pada Paguyuban Wonogiri Manunggal Sedya (PAWONMAS) - Wahyono, Wahyono; Widhiastuti, Hardani; Pratiwi, Shinta (IPM2KPE, 2024)
The aim of this study is to the direct correlation between leadership and role conflict with the trust of organizational members and indirect correlation through the role of sense of community as an intervening variable in the Paguyuban Wonogiri Manunggal Sedya (Pawonmas) organization. The research method was quantitative with a cross-sectional approach and used path analysis method using SMART-PLS. According to the study's findings, the majority of respondents (65%) have been members for five to eight years, and 41% are between the ages of 46 – 55 year old. Member trust is strongly correlated with leadership, role conflict, and sense of community; however, sense of community does not have a strong role in the indirect correlation between leadership and role conflict and member trust. In conclusion, it is necessary to attempts the sense of community among members in order to strengthen members' trust in the organization. Keywords: Leadership, Role Conflicts, Member’s Trust, Sense of Community, Pawonmas